Structural uncertainty in onchocerciasis transmission models influences the estimation of elimination thresholds and selection of age groups for seromonitoring - Hamley,J; Walker,M; Coffeng,LE; Milton,P; de,Vlas SJ; Stolk,WA; Basanez,M-G (Journal of Infectious Diseases, 2020)
Background. The World Health Organization recommends monitoring Ov16 serologyin children aged <10 years for stopping mass ivermectin administration. Transmission models can help to identify the most informative age groups for serological monitoring and investigate the discriminatory power of serology-based elimination thresholds.Model predictions will depend on assumed age-exposure patterns and transmission efficiency at low infection levels. Methods. The individual-based transmission model, EPIONCHO-IBM, was used toassess: i) the most informative age groups for serological monitoring using receiveroperator characteristic curves for different elimination thresholds under various age-dependent exposure assumptions, including those of ONCHOSIM (another widely-used model), and ii) the influence of within-human density-dependent parasite establishment (included in EPIONCHO-IBM but not in ONCHOSIM) on positive predictive values for different serological thresholds.Results. When assuming EPIONCHO-IBM exposure patterns, under-10s are themost informative age group for seromonitoring; when assuming ONCHOSIM’s exposure patterns, 5–15-year olds are the most informative (as published elsewhere).Omitting density-dependent parasite establishment results in more lenientseroprevalence thresholds, even for higher baseline infection prevalence and shorter treatment durations.Conclusions. Selecting appropriate seromonitoring age groups depends critically onage-dependent exposure patterns. The role of density dependence on elimination thresholds largely explains differing EPIONCHO-IBM and ONCHOSIM elimination predictions.